Prioritas Tanaman Pangan Unggulan Sub Sektor Pertanian Di Kabupaten Kendal Periode 2014-2022 - Wibowo, Hendri; Dewi Hastuti; Heri Kustanto; Putri Wulan Arum Nudin (Universitas Negeri Padang, 2025)
The purpose of this study is to analyze food crop priorities using assessment criteria from the Location Quotient analysis and Shift Share analysis of Kendal Regency. The analysis methods used in the study are Location Quotient and Shift Share. The data used in determining these priorities are from time series data in Kendal Regency. The results of the Location Quotient analysis show that Sukorejo District is the only area that has four superior commodities, namely soybeans, peanuts, cassava, and sweet potatoes. Meanwhile, based on the Shift Share analysis, there are 2 districts that have superior commodities, namely South Kaliwungu District has three commodities with rapid growth, namely peanuts, green beans, and sweet potatoes, while Patebon District excels in rice, corn, and green beans. In addition, corn commodities in Patean, Gemuh, and Kangkung Districts are categorized as priority 1 because they have a major contribution to driving economic growth in the agricultural sector in the area